PENINGKATAN LITERASI KEUANGAN KELOMPOK USAHA ASLI DESA MELALUI PELATIHAN PENGELOLAAN KEUANGAN - Azhar, Rialdi; Firdaus, Luthfi; Waspodo, Lego (Faculty of Economics and Business Lampung University, 2024)
The training followed by financial management mentoring aims to provide insights and skills, focusing on enhancing financial management capacity through continuous mentoring and guidance. The training and mentoring activities in financial management will be conducted through a series of sessions covering basic financial management understanding, budget planning and control, as well as resource and information management techniques. Following the training sessions, participants will be guided and mentored in applying the acquired knowledge to their respective organizations. The expected outcome of this activity is to assist financial managers in improving performance and reducing financial risks within their organizations. This financial management training and mentoring activity can help native entrepreneurs in rural areas improve performance and ensure the sustainability of organizational financial management.